An Updated Analysis of the Pediatric Section of the Orthopaedic In-Training Examination. Issue 10 (November 2020) - Ellsworth, Bridget K.; Premkumar, Ajay; Shen, Tony; Lebrun, Drake G.; Cross, Michael B.; Widmann, Roger F.
Abstract : Background: An updated analysis of the pediatrics section of the Orthopaedic In-Training Examination (OITE) is helpful for resident education and preparation for the OITE. The purpose of this study is to provide an updated evaluation of the pediatric category of the OITE, and to explore trends in question topics and taxonomy compared with the previously published analysis from 2011 to 2014. Methods: Five years (2015-2019) of OITE questions, answers, and references were reviewed. The number of pediatric questions per year was recorded, and questions were subcategorized based on topic tested. The presence or absence of imaging or a clinical photograph was noted. Each question was also assigned a cognitive taxonomy level, based on a previously published classification system. Results: The percentage of pediatric questions on the 2015-2019 OITEs averaged 11.4% compared with 12.6% from 2011 to 2014 ( P =0.349). The 3 most commonly tested pediatric topics were general trauma (17.8%), elbow trauma (13.2%), and genetic disorders/syndromes (11.2%). There was a significant increase in questions that required diagnosis and interpretation (27.6% vs. 8%, P <0.001) and a slight but not significant decrease in the questions requiring simple knowledge recall (26.3% vs. 35.5%, P =0.120) and decisions about management (46.1% vs. 56.5%, P =0.077). Overall, 65% of questions utilized clinical photographs or imaging studies compared with 62% from 2011 to 2014 ( P =0.621). The most common references were the Journal of Pediatric Orthopaedics, Journal of American Academy of Orthopaedic Surgeons, and Journal of Bone and Joint Surgery . Textbooks were cited less frequently than in the past. Conclusions: While the percentage of pediatric questions on the OITE has remained consistent over time, the percentage of questions requiring diagnosis and interpretation has increased. In addition, questions testing genetic disorders/syndromes have become more prevalent in recent years. The most commonly cited resources were high-impact journal articles, with textbooks cited less frequently than in previous years. Clinical Relevance: Knowledge of the most frequently tested topics and resources cited may assist orthopaedic residents in preparing for the OITE and orthopaedic faculty to focus didactic sessions on the most commonly tested topics.